2005
DOI: 10.2169/internalmedicine.44.554
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Hematological Disorders Caused by Copper Deficiency during Long-Term Enteral Nutrition

Abstract: Objective Copper deficiency has been reported to cause hematological disorders. However, its clinical and hematological characteristics are not fully understood. Therefore, we investigated bedridden patients suffering from copper deficiency and tried to clarify the clinical features of hematological disorders caused by this condition.Patients and Methods Five patients with typical copper deficiency who had been dependent upon enteral nutrition for a long period of time due to various diseases were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 26 publications
1
18
0
6
Order By: Relevance
“…Also, Nagano et al shows that copper supplementation decreased MCV levels in humans. 20 At the same time the results show that the negative correlation is between serums copper concentration and ferritin, hemoglobin values of serum in this study (r= -0.203 p<0.01, r= -0.392 p<0.001 respectively). We observed that high copper negatively affected hematological parameters in this research.…”
Section: Groupssupporting
confidence: 61%
“…Also, Nagano et al shows that copper supplementation decreased MCV levels in humans. 20 At the same time the results show that the negative correlation is between serums copper concentration and ferritin, hemoglobin values of serum in this study (r= -0.203 p<0.01, r= -0.392 p<0.001 respectively). We observed that high copper negatively affected hematological parameters in this research.…”
Section: Groupssupporting
confidence: 61%
“…Neutropenia has been described previously in copper deficiency (18) and may be due to arrested maturation of granulocytes (19). Grade 3 to 4 neutropenia was also seen in the phase II study of tetrathiomolybdate (16).…”
Section: Discussionmentioning
confidence: 58%
“…Such patients sometimes have trace element deficiencies, and the clinical sequelae of these deficiencies may not be very obvious (3,4). Some such patients have anemia, often caused by iron deficiency due to gastrointestinal bleeding, but severe copper deficiency usually presents with anemia and or leucopenia (5)(6)(7). There have been reports of ringed sideroblasts and vacuolation of erythroid and myeloid precursors in patients with severe copper deficiency (6,(8)(9)(10)(11)(12)(13)(14)(15)…”
Section: Introductionmentioning
confidence: 99%